Predictive Value of Cord Blood Bilirubin for Hyperbilirubinemia in Term Neonates with ABO Incompatibility - Sharma, Subas; Sapkota, Bishal (Nepal Journal of Health Sciences, 2024)
Introduction: Jaundice affects 60% of full-term and 80% of preterm neonates. Feto-maternal ABO incompatibilities occur in 20-25% of pregnancies, but severe haemolytic disease develops in only 10%. ABO-incompatible babies have doubled the risk of jaundice requiring treatment and a 5-10 times increased risk of exchange transfusions. Objective: Aim of this study was to determine if cord blood bilirubin (CBB) can predict hyperbilirubinemia in term babies with ABO setup prior to discharge that would help to decrease readmission and subsequently complications due to jaundice. Methods: A hospital-based prospective observational study was conducted at Patan Hospital. Cord blood group and bilirubin levels were collected from newborns of O positive mothers. Babies with A positive and B positive blood groups had their CBB levels measured and were followed daily for 72 hours. Serum bilirubin was tested based on clinical judgment to detect hyperbilirubinemia and treated per NICE guidelines. Data were analysed using SPSS v21.0, Mann-Whitney test, ANOVA, and ROC analysis. Results: Among 66 cases, significant hyperbilirubinemia was seen in 7 neonates (10.6%). It was more common in B positive babies (12.2%) compared to A positive (8%). Mean CBB was 3.45 ± 0.57 in those developing significant hyperbilirubinemia. A CBB of 2.95 mg/dL had the highest sensitivity (86%), specificity (94%), and negative predictive value (98%) for predicting hyperbilirubinemia in ABO setup babies. Conclusion: Term babies with ABO incompatibility and CBB<2.95 mg /dL are unlikely to need further evaluation, while those with cord bilirubin level ≥2.95 mg/dL should have frequent early follow-ups.